2010
DOI: 10.1007/s11172-010-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of iridium bis(phosphinite) pincer complexes with protic acids

Abstract: Iridium pincer complexes [C 6 H 3 2,6 (OPBu t 2 ) 2 ]Ir(H)Cl (10) and [4 EtOOCC 6 H 2 2,6 (OPBu t 2 ) 2 ]Ir(H)Cl (11) react with protic acids undergoing metallation of one of the tert butyl groups to form double cyclometallated products [4 R C 6 H 2 2 (OPBu t 2 ) 6 (OP(Bu t )CMe 2 CH 2 )]IrCl (12, R = H; 13, R = COOEt), which are stable in air. Complex 12 reacts with CO and Bu t NC giving the corresponding 18 electron complexes [C 6 H 3 2 (OP Bu t 2 ) 6 (OP(Bu t )CMe 2 CH 2 )]Ir(L)Cl (14, L = CO; 15, L = CNBu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Upon cooling, these resonances decoalesced into two pairs of sharp signals, which are attributed to the two sets of NHC C–H and N–Me groups (one proximal and one distal to the CO ligand; Figure , inset). The infrared spectrum of 5b exhibits one carbonyl band with a stretching frequency appropriate for a cationic Ir III monocarbonyl (2024 cm –1 ) . The complex [Cp*Ir­(PMe 3 )­Me­(CO)] + shows a higher value for ν CO (2035 cm –1 ), consistent with the assertion that 3b is more electron-rich than its PMe 3 -ligated counterpart.…”
Section: Resultssupporting
confidence: 66%
“…Upon cooling, these resonances decoalesced into two pairs of sharp signals, which are attributed to the two sets of NHC C–H and N–Me groups (one proximal and one distal to the CO ligand; Figure , inset). The infrared spectrum of 5b exhibits one carbonyl band with a stretching frequency appropriate for a cationic Ir III monocarbonyl (2024 cm –1 ) . The complex [Cp*Ir­(PMe 3 )­Me­(CO)] + shows a higher value for ν CO (2035 cm –1 ), consistent with the assertion that 3b is more electron-rich than its PMe 3 -ligated counterpart.…”
Section: Resultssupporting
confidence: 66%
“… 10 During the formation of 4 from 1 , three C sp 3 –H bonds are activated intramolecularly in addition to one external C sp 2 –H bond. Cyclometallation of tert -butyls 11 or other groups 12 , 13 bound to phosphorus is not unprecedented in the chemistry of iridium pincer complexes, but in the case of 4 it results in the formation of a new C–C double bond. To the best of our knowledge, this is the first example where the main product is the result of the formation of a C–C double bond from non-activated C sp 3 –H bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has also shown that in the cationic complexes [(POCOP)Ni(NCMe)] + the P -substituents have greater influence on structures and reactivities relative to chloride substituents at the 3- and 5-positions (with respect to the metallated carbon) . In contrast to these sporadic and limited studies for POCOP-Ni systems, the impact of ring- and P -substituents on the properties of POCOP-Ir complexes has been investigated in much more detail . Similar studies have been reported on NCN-Ni and NCN-Pt complexes …”
Section: Introductionmentioning
confidence: 99%